Grain-size analysis obtained from sediment core RD04 (island of Sylt) - Nina Lenz; Sebastian Lindhorst (PANGAEA, 2021)
Core RD04 originates from a natural back-barrier marsh (island of Sylt). The marsh in Sylt is a low-energy, back-barrier marsh. Grain-size data were used to determine and quantify multiple sedimentary processes by the application of end-member modelling.
In: Lenz, N; Lindhorst, S (2021): Grainsize analysis and radionuclide measurements (210Pb, 137Cs, 226Ra) obtained from sediment cores RD04 (island of Sylt), BT02 and BT03 (Eiderstedt peninsula; south-eastern North Sea) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.933869